2012
DOI: 10.1029/2011rs004794
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the sprite polarity paradox: The role of halos

Abstract: [1] This study revisits the sprite polarity paradox, first manifest by observations that exceptional cloud-to-ground flashes with negative polarity generally did not produce detectable sprites. The paradox is here resolved by the Transient Luminous Event (TLE) known as the halo, which on account of its inferior brightness (0.3 MR versus 1.5 MR) and substantially shorter duration (1 ms versus 10-100 ms) in comparison with the sprite, is not readily detectable in ground-based video cameras with standard field du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 74 publications
(138 reference statements)
9
94
1
Order By: Relevance
“…Rare observations of sprites associated with À CG discharges seem to contradict the proposed Wilson's hypothesis of initiations of sprites based on electric field calculations, however, the observation of halos by ISUAL payload and ground based PIPER system show abundance of halos associated with ÀCG discharges (Frey et al, 2007;Williams et al, 2012). Using ground based Table 2 Summary of emissions from sprites (after: Liu et al, 2006;Pasko, 2007).…”
Section: Spritesmentioning
confidence: 73%
See 4 more Smart Citations
“…Rare observations of sprites associated with À CG discharges seem to contradict the proposed Wilson's hypothesis of initiations of sprites based on electric field calculations, however, the observation of halos by ISUAL payload and ground based PIPER system show abundance of halos associated with ÀCG discharges (Frey et al, 2007;Williams et al, 2012). Using ground based Table 2 Summary of emissions from sprites (after: Liu et al, 2006;Pasko, 2007).…”
Section: Spritesmentioning
confidence: 73%
“…Because of smaller SIR associated with À CG discharges, streamer formation/development is hindered and hence sprite structure is rarely observed in association with À CG discharges, but halos are observed. Recent observations with improved temporal and intensity resolutions (Newsome and Inan, 2010;Williams et al, 2012) and modeling studies (Asano et al, 2008(Asano et al, , 2009) indicated that both þCG and À CG discharges are equally capable of triggering discharges in the mesosphere (sprites and halos). However, streamer evolution/development strongly depends on electric field and local electron density profile (Qin et al, 2011(Qin et al, , 2012a(Qin et al, , 2012b.…”
Section: Emission Band Systemmentioning
confidence: 97%
See 3 more Smart Citations